Finishing coatings with reflective nanomaterials: a path to energy-efficient buiildings - Rita Carvalho Veloso (2022)
The growing concern about energy issues in buildings, namely related to cooling needs, has led to the search for new constructive solutions. Thus, there is a continuous increase in the implementation of exterior thermal insulation systems, such as ETICS1 . In the assessment of the durability of these systems, there is a growing demand for hygrothermal comfort studies though very few reports are available regarding their optical properties. Progressively, solutions are being required with darker colours2 , so that the incorporation of nanomaterials might be a possible solution. The optical and catalytic capacity turns nanomaterials into excellent candidates for use in finishing coatings with high solar reflectance with dark colours, without affecting the aesthetic characteristics, thus improving the durability of such coatings 3,4 . Our study targeted the development of innovative envelope systems by increasing their solar reflectance through new finishing coatings formulations with the inclusion of nanoparticles. For that, it is necessary to develop and optimize nanoparticles formulations to achieve a high NIR reflectance. A preliminary study was conducted, demonstrating that the spectral reflectance of a conventional black colorant doped with different nanoparticles with the concentration in the coating being varied (1%, 3%, 5%, 8%, 12%, 16% and 20%), in an acrylic substrates, was increased. Such optical behaviour of the doped black colorant samples was experimentally evaluated through spectral reflectance calculations using a modular spectrophotometer to understand the relation between these properties and the morphological and structural characteristics of the nanoparticles. The results obtained can help formulating new finishing coatings with increased near-infrared reflectance of buildings façades, using, for instance, more than one type of nanoparticles.